Suicide and Youth: Risk Factors - Bilsen, Johan (Frontiers in Psychiatry, 2018)
Suicide occurs more often in older than in younger people, but is still one of the leading causes of death in late childhood and adolescence worldwide. This not only results in a direct loss of many young lives, but also has disruptive psychosocial and adverse socio-economic effects. From the perspective of public mental health, suicide among young people is a main issue to address. Therefore we need good insight in the risk factors contributing to suicidal behavior in youth. This mini review gives a short overview of the most important risk factors for late school-age children and adolescents, as established by scientific research in this domain. Key risk factors found were: mental disorders, previous suicide attempts, specific personality characteristics, genetic loading and family processes in combination with triggering psychosocial stressors, exposure to inspiring models and availability of means of committing suicide. Further unraveling and knowledge of the complex interplay of these factors is highly relevant with regard to the development of effective prevention strategy plans for youth suicide.